AIM2 inflammasome activation benefits the therapeutic effect of BCG in bladder carcinoma - Zhou, Houhong; Zhang, Lei; Luo, Weihan; Hong, Huaishan; Tang, Dongdong; Zhou, Dewang; Zhou, Lingli; Li, Yuqing (Frontiers in Pharmacology, 2022)
A large proportion of bladder cancer (BLCA) patients suffer from malignant progression to life-threatening muscle-invasive bladder cancer (MIBC). Inflammation is a critical event in cancer development, but little is known about the role of inflammation in BLCA. In this study, the expression of the innate immune sensor AIM2 is much lower in high-grade BLCA and positively correlates with the survival rates of the BLCA patients. A novel AIM2 overexpressed BLCA model is proposed to investigate the impact of AIM2 on BLCA development. Mice inoculated with AIM2-overexpressed cells show tumor growth delay and prolonged survival compared to the control group. Meanwhile, CD11b+ cells significantly infiltrate AIM2-overexpressed tumors, and AIM2-overexpression in 5637 cells enhanced the inflammasome activation. In addition, oligodeoxynucleotide (ODN) TTAGGG (A151), an AIM2 inflammasome inhibitor, could abolish the elevation of AIM2-induced cleavage of inflammatory cytokines and pyroptosis. Orthotopic BLCA by AIM2-overexpressed cells exhibits a better response to Bacillus Calmette-Guérin (BCG) immunotherapy. Overall, AIM2 inflammasome activation can inhibit the BLCA tumorigenesis and enhance the therapeutic effect of BCG in BLCA. This study provides new insights into the anti-tumor effect of AIM2 inflammasome activation in BLCA and the immunotherapeutic strategy of BLCA development.